Der Leopoldstädter Tempel: eine Dokumentation - Karplus, Hermann David (Sitzungsberichte, 2025)
The Tempelgasse synagogue in Vienna, designed by Ludwig Förster and built between 1852 and 1858, marked a milestone in the annals of Jewish emancipation and architectural history. Located on a narrow alley in what was then the suburb of Leopoldstadt, it was planned to be the first monumental replica of King Solomon's Temple. Built in a Moorish-Oriental style and with an original projected capacity of 2,240 worshipers, making it Vienna'slargest synagogue,thetemple in Leopoldstadt was consecrated on June 15, 1858 in a festive ceremony during which a cornerstone brought from Jerusalem was laid.Yet the project stirred up a controversy: it deviatedfromtraditional OrthodoxJewishpractices by seeking to reflecttheviewpoints of the evolvingReform Jewish communities of the time. The construction and utilization ofthis unusualstructurethus became a long and intricate affair. In 1917, a major fire destroyed significant parts of the building, necessitating four years of restoration work, which ended in1921. The LeopoldstädterTemple, wheresuchfamous scholars as Adolf Jellinek and Moritz Güdemanndelivered their sermons,did not escape the Nazis' wrath andwas destroyedduringthe 1938night of pogroms,known as the"Kristallnacht".In his book,Dr. HermannDavidKarplus describes the situation of the Jews in Vienna at the time,providing detailed data and insights intothe history of the constructionof thebuilding,elaborating onthe highly interestingritualdisputeandthedisputeoverthe use of theorgan,andoffering biographical notes onthe community'smostnotablepublic figures:rabbis and preachers, cantors,andother officials. He unearthedplans and documentsfromthe archives of the Vienna Jewish Community in Jerusalem that werebelievedto have been lost. Numerous high-resolution scansoffacsimiles, photos,anddesignplans arenowavailable toresearchers and other interested parties throughthe publisher's digital archive